Developing final product specifications for long-grain parboiled rice (Oryza sativa L.) based on South African consumer preference - Slogrove, Desre Anne (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScFoodSc) -- Stellenbosch University, 2014.